2020
DOI: 10.1002/alz.12117
|View full text |Cite
|
Sign up to set email alerts
|

Sleep characteristics and cerebrospinal fluid biomarkers of Alzheimer's disease pathology in cognitively intact older adults: The CABLE study

Abstract: Introduction This study tested the self‐reported sleep characteristics associated with cerebrospinal fluid (CSF) Alzheimer's disease (AD) biomarkers in cognitively intact older adults. Methods The linear and non‐linear regression analyses were conducted in 736 cognitively normal participants (mean [standard deviation; SD] age, 62.3 [10.5] years, range 40 to 88 years, 59% female) who had measurements of cerebrospinal fluid (CSF) amyloid beta (Aβ) and tTau proteins and sleep characteristics, after adjusting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…In cognitively unimpaired older adults, various sleep parameters have been associated with greater global Aß levels measured in the CSF or using PET, including poorer self-reported sleep quality, both cross-sectionally (Sprecher et al, 2017) and longitudinally (Fjell et al, 2018), longer subjective (Brown et al, 2016) and objective (Ettore et al, 2019) sleep latency, both insufficient and long self-reported sleep duration (Spira et al, 2013;Xu et al, 2020), lower sleep efficiency (Ettore et al, 2019;Ju et al, 2013;Molano et al, 2017), increased sleep fragmentation (Ettore et al, 2019;Lucey et al, 2019;Wilckens et al, 2018), excessive daytime sleepiness (Xu et al, 2020), and altered slow wave activity (SWA) (Ju et al, 2017;Varga et al, 2016;Winer et al, 2019) (Table 1). Furthermore, Mander et al, (2015) showed that amyloid burden in medial prefrontal areas disrupts SWA, negatively affecting sleep-dependent memory consolidation.…”
Section: Sleep and Amyloid Pathologymentioning
confidence: 99%
“…In cognitively unimpaired older adults, various sleep parameters have been associated with greater global Aß levels measured in the CSF or using PET, including poorer self-reported sleep quality, both cross-sectionally (Sprecher et al, 2017) and longitudinally (Fjell et al, 2018), longer subjective (Brown et al, 2016) and objective (Ettore et al, 2019) sleep latency, both insufficient and long self-reported sleep duration (Spira et al, 2013;Xu et al, 2020), lower sleep efficiency (Ettore et al, 2019;Ju et al, 2013;Molano et al, 2017), increased sleep fragmentation (Ettore et al, 2019;Lucey et al, 2019;Wilckens et al, 2018), excessive daytime sleepiness (Xu et al, 2020), and altered slow wave activity (SWA) (Ju et al, 2017;Varga et al, 2016;Winer et al, 2019) (Table 1). Furthermore, Mander et al, (2015) showed that amyloid burden in medial prefrontal areas disrupts SWA, negatively affecting sleep-dependent memory consolidation.…”
Section: Sleep and Amyloid Pathologymentioning
confidence: 99%
“…Several mechanisms may explain the impact of sleep duration on cognition. Short sleep duration correlates with many pathologies that lead to lower cognition, such as impaired β-amyloid (Aβ) clearance, pathological tau, impaired synaptic plasticity, atrophy of the cortex, and circadian rhythm disturbances (Yaffe et al, 2014;Malkani and Zee, 2018;Xu et al, 2020). Long sleep duration is also associated with sleep fragmentation and chronic inflammation, which are linked to lower cognition (Lin et al, 2018;Wilcox et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms could explain the impact of sleep duration on cognition. Short sleep duration correlated with many pathologies which would lead to lower cognition, such as impaired β-amyloid (Aβ) clearance, pathologic tau, impaired synaptic plasticity, and circadian rhythm disturbances 33-35 . Long sleep duration was associated with sleep fragmentation and chronic inflammatory, which were associated with lower cognition 36,37 .…”
Section: Discussionmentioning
confidence: 99%